Capacity building for fish processors - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Sirah Njie describes the training and organisation of women fish processors in The Gambia, which is being carried out by an international project.